2024
DOI: 10.1101/2024.01.11.574849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Network-Assisted Humanization of COVID-19 Hamster scRNAseq Data Reveals Matching Severity States in Human Disease

Vincent D Friedrich,
Peter Pennitz,
Emanuel Wyler
et al.

Abstract: Translating findings from animal models to human disease is essential for dissecting disease mechanisms, developing and testing precise therapeutic strategies. The coronavirus disease 2019 (COVID-19) pandemic has highlighted this need, particularly for models showing disease severity-dependent immune responses. Single-cell transcriptomics (scRNAseq) is well poised to reveal similarities and differences between species at the molecular and cellular level with unprecedented resolution. However, computational met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(98 reference statements)
1
0
0
Order By: Relevance
“…Similar trends were observed when comparing blood neutrophils between Roborovski and Syrian hamsters. 62 Based on this finding, our data clearly link inflammatory neutrophils to disease severity and align with previous studies in which we showed that dampening neutrophilic inflammation by dexamethasone treatment prevents lethal disease outcomes. 63 Moreover, inflammatory neutrophils in severely diseased Roborovski hamsters strongly expressed Cd274, as do human neutrophils in patients with a severe disease course.…”
Section: Discussionsupporting
confidence: 91%
“…Similar trends were observed when comparing blood neutrophils between Roborovski and Syrian hamsters. 62 Based on this finding, our data clearly link inflammatory neutrophils to disease severity and align with previous studies in which we showed that dampening neutrophilic inflammation by dexamethasone treatment prevents lethal disease outcomes. 63 Moreover, inflammatory neutrophils in severely diseased Roborovski hamsters strongly expressed Cd274, as do human neutrophils in patients with a severe disease course.…”
Section: Discussionsupporting
confidence: 91%